A formação do trabalho (Bildung) e o trabalho da formação (Formieren): a educação da consciência desde a certeza sensível até a dominação e escravidão, na obra Fenomenologia do espírito de Hegel 1807 - Cleudio Marques Ferreira (2003)
This study proposes a thorough look at the Formation of Work and the Work of Formation: the education of conscience from Sensitive Certainty to Domination and Slavery. The natural conscience, in its journey of formation, submerges in the doubt and desperation of lacking congruence between what is known and the truth of the object. In this way, the formation of the work of the conscience is in the relation of the experience between what one knows and the truth that is overcome by the figures of Sensitive Certainty and of Perception, up to Force and Understanding. Through this last figure is initiated the process of subjectivity, in which there is an identification between knowing the subject and knowing the object that unfolds into two self-consciousnesses. Thus, it passes through the work of formation in which a conscience, submitted to life, puts itself to work in the building of the object to serve its master, having lost its being-for-itself in the struggle between life and death. The process of reuniting the being-for-itself of the slave and the intuition of ones intrepidness pass through the absolute fear of death, by service and by work, being that it is in the latter that it implements the reuniting of its for-itself, when internalizing its for-itself and externalizing the creation of the shape of the object by its work, substituting rough object with its creation, which he contemplates as a sign of his being in the world. There is, therefore, the forming (Formieren), whereas the process of the work appears as one of two stages of formation (Bildung).